Anomalous vasculature in the neck diagnosed by ultrasound. Issue 4 (2nd June 2020) - Constantine, Sarah; Roach, Denise
Abstract: Anomalous vascular anatomy was detected in the neck of a 52‐year‐old female with a Klippel–Feil anomaly. Ultrasound identified three separate arteries in the left carotid sheath without any branching or bifurcations. The vascular waveforms were used to identify the vessels as the internal carotid artery, external carotid artery and vertebral artery. This rare vascular anomaly was confirmed with CT angiography.